Assessment of tobacco control advocacy behavioural capacity among public health faculty and students: a cluster intervention study. (December 2018) - Wu, D.; Yang, T.; Stillman, F.A.; Guo, W.; Zhou, H.; Feng, X.
Abstract: Objectives: This study assessed the outcomes of a tobacco control advocacy behavioural capacity (ABC)–building programme among public health faculty and students in China. Study design: This is a cluster intervention study with subjects matching in the different stages of the intervention and observation. Methods: Public health students (n = 1046) and faculty (n = 199) were recruited in the intervention group. The intervention included a series of tobacco control advocacy curriculum and activities that were developed and implemented at schools or departments of public health in 22 universities across China. The control group participants (n = 540) were public health undergraduate students from another 11 universities selected from the different geographic regions. A comprehensive assessment tool was used to measure the tobacco control ABC and perceived stress level to compare changes at baseline, midterm and 12-month follow-up. Repeated measures analysis of variance, paired t tests and chi-squared tests, general linear model and generalized estimating equation were used to determine the time effect for targeted students and faculty. Multivariate analysis of variance and logistic regression model were conducted to evaluate the treatment effects for students between intervention and control sites. Results: Nine hundred and thirty-seven students and 170 faculty members in the intervention group and 469 students in the control group were valid for the final evaluation. Findings from treatment effect analyses show that the capacity-building programme significantly improved public health students' ABC, including awareness of tobacco control messages (F = 107.65, P < 0.01), general and public heath tobacco control attitudes (F = 7.52, P < 0.01; F = 8.53, P < 0.01), advocacy interest and motivation (F = 10.11, P < 0.01) and public advocacy behaviour for both family members and relatives or friends. The perceived stress in the intervention group students was also reduced significantly in comparison with the control group students (F = 4.99, P < 0.01). For faculty members, their ABC except advocacy for family members was all increased by time effect analyses. The training programme did not impact faculty and students' smoking behaviour. Conclusions: This study provided evidence to support the implementation of tobacco control advocacy capacity training among public health professionals and students to curb the tobacco epidemic in China. Highlights: A tobacco control advocacy behavioural capacity (ABC) building programme was scaled up to 22 universities across China. This programme improved the ABC behavioural capacity among both public health faculty and students. Participating in this programme can significantly alleviated students' perceived stress as an additional positive outcome.